Bismuth Oxide-Based Photocatalytic Nanoplatforms for Cancer Theranostics - Advances, Mechanisms, and Clinical Prospects - Reyhan Natadilandes; Wardah Ibnatis Tsaniyah; Lathifah Puji Hastuti; Suseno Amien (Indonesian Journal of Chemical Studies, 2026)
The growing demand for precise, minimally invasive, and image-guided cancer management has accelerated the development of multifunctional theranostic platforms capable of unifying diagnosis and therapy. Among emerging inorganic nanomaterials, bismuth oxide (Bi2O3) has gained significant attention due to its high atomic number, strong X-ray attenuation, tunable semiconductor band structure, and intrinsically favorable biocompatibility. This review provides a synthesis of advances in Bi2O3-based photocatalytic nanoplatforms for cancer theranostics. This article discusses how phase control, defect engineering, doping, and heterojunction construction enable enhanced ROS generation, improved charge separation, broadened optical absorption, and synergistic radiosensitization. These physicochemical features underpin a wide range of theranostic applications, including CT, photoacoustic, and multimodal imaging (photodynamic-, sonodynamic-, and photothermal-type therapies), radiotherapy enhancement; controlled chemotherapy delivery; and emerging immunomodulatory strategies. State-of-the-art designs increasingly integrate hierarchical architectures, oxygen-vacancy engineering, NIR-responsive components, and tumor microenvironment–activated functionalities to achieve intelligent, multi-stimuli cancer treatment. Despite their promise, key translational challenges persist, particularly relating to long-term biodistribution, clearance, standardized manufacturing, and regulatory validation. By consolidating mechanistic insights and engineering principles, this review outlines design guidelines for the rational development of clinically viable Bi2O3-based nanoplatforms and highlights their potential to bridge diagnostic imaging with personalized, multi-modal cancer therapy.